p53–GSDME Elevation: A Path for CDK7 Inhibition to Suppress Breast Cancer Cell Survival - Wang, Yueyuan; Peng, Jingyu; Mi, Xuguang; Yang, Ming (Frontiers in Molecular Biosciences, 2021)
Higher cyclin-dependent kinase (CDK7) expression is a character of breast cancer and indicates poor prognosis. Inhibiting CDK7 exhibited effective cancer cell suppression which implies the potential of CDK7 inhibition to be a method for anti-cancer treatment. Our study aimed to explore a novel mechanism of CDK7 inhibition for suppressing breast cancer cell survival. Here, we proved inhibiting CDK7 repressed breast cancer cell proliferation and colony formation and increased the apoptotic cell rate, with p53 and GSDME protein level elevation. When p53 was suppressed in MCF-7 cells, the decline of GSDME expression and associated stronger proliferation and colony formation could be observed. Since downregulation of GSDME was of benefit to breast cancer cells, p53 inhibition blocked the elevation of GSDME induced by CDK7 inhibition and retrieved cells from the tumor suppressive effect of CDK7 inhibition. Therefore, CDK7 inhibition exerted a negative effect on breast cancer cell proliferation and colony formation in a p53–GSDME dependent manner. These results revealed the CDK7–p53–GSDME axis could be a pathway affecting breast cancer cell survival.